Measuring the Usability and Appeal of an E-Module Using the User Experience Questionnaire - Abdurrahman, Nabil; Soeprijanto, Soeprijanto; Muksin, Muksin (Journal of Educational Sciences, 2025)
This study aims to assess the readability level of an interactive e-module developed specifically for the Basic Electrical Engineering subject. The research sample consisted of students from three vocational schools in Jakarta. Prior to field implementation, the e-module underwent a validation phase involving six experts: two subject matter experts in electrical engineering, two experts in educational media technology, and two language experts specializing in Indonesian for secondary education. The study employed a Research and Development (R&D) methodology using the DDD-E model developed by Ivers & Barron. The validation results demonstrated that all assessed aspects were rated as “valid” by material, media, and language experts. Furthermore, the results of the User Experience Questionnaire (UEQ) revealed the following mean scores: Attractiveness (2.15), Perspicuity (1.94), Efficiency (2.14), Dependability (2.16), Stimulation (2.05), and Novelty (2.11). Based on the responses from 87 participants, the developed interactive e-module was rated in the “Excellent” category across all six aspects, indicating its strong potential and readiness for use in instructional settings.